Assessment of Regenerated Bioscaffold Mitral Valve Annulus Extracellular Matrix Components from a Juvenile Non-human Primate Model. (9th April 2021) - Gonzalez, Brittany A.; Gonzalez Perez, Marcos; Scholl, Frank; Bibevski, Steve; Ladich, Elena; Rivas Wagner, Krishna; Bibevski, Jennifer; Hernandez, Lazaro; Morales, Pablo; Lopez, Jesus; Ramaswamy, Sharan
Abstract : Objective : Critical congenital heart valve disease (CCHVD) in the young has limited treatment options due to sizing options and lack of growth. To assess somatic growth potential, we implanted a bioscaffold mitral valve comprising of porcine small intestinal submucosa (PSIS) in a juvenile baboon model. Methods : Juvenile baboons (n=3) were implanted with a hand-made PSIS (Cormatrix, Roswell, GA) mitral valve. The PSIS valves were excised at 3-, 11- and 20-months post-implantation for histological assessment. In brief, the explants were fixed in 10% Formalin (w/v), paraffin embedded and stained with Movat's Pentachrome (Movat's; Alizée Pathology, Inc., Thurmont, MD). These histological images were subsequently thresholded, normalized, color segmented (ImageJ, NIH) and spatially mapped for quantification of ECM components (MATLAB; Mathworks, Natick, MA). Results : We found that PSIS bioscaffold mitral valves annulus integrated with the myocardium and was comprised of collagen, proteoglycans, elastin and fibrin (Figure 1 ). Interestingly there was no significant difference (p>0.05) between any of the extracellular matrix (ECM) proteins, except proteoglycans; the 3-month explant had a significantly lower (p<0.05) amount of proteoglycans compared to both the 11- and 20-month explants. Conclusions : Our findings suggest that the PSIS bioscaffold mitral valve apparatus can regenerate the annulus of the mitral valve without additional treatment but at an early time point (3-months) could not produce comparable amounts of de novo proteoglycans. Additional treatments to the bioscaffold in vitro (e.g. stem cell incorporation) may enhance the ECM production once implanted